THE IMPLEMENTATION OF “WRITING IN PAIRS” BASED ON STUDENTS’ PERCEPTION - lailatul husna (Universitas Putera Batam, 2018)
Writing skills is one of four skills that a student learns in language. Writing is a language skill with the last sequence studied by the learner. Writing in pairs is a strategy which is applied in writing. The aims of writing in pairs in learning are students and their partners can work together to get unite ideas owned by each student. This study was conducted to see how the use of writing in pairs strategy in learning writing that viewed from students perception whose results can be used as a reference for improvement in learning writing skills. The data were taken from the Essay Writing class in the English Language Education Study Program of FKIP Bung Hatta University by giving questionnaires to the students after they have studied three times of writing learning experience with writing in pairs strategy or pair work. The results showed that students were happy with the paired work strategy in writing activities. Working in pairs, learners find that it is easier to come up with an idea so that the boring writing activity is turning into a more fun activity.